Ecohydrologic modeling of crop evapotranspiration in wheat (Triticum-aestivum) at sub-temperate and sub-humid region of India - Kumar, Rohitashw (International Journal of Agricultural and Biological Engineering, 2013)
Abstract: Efficient water management of crop requires accurate irrigation scheduling which, in turn, requires the accurate measurement of crop water requirement. Reference evapotranspiration plays an important role for the determination of water requirements for crops and irrigation scheduling. Various models/approaches varying from empirical to physically base distributed are available for the estimation of reference evapotranspiration. This study identified most suitable reference evapotranspiration model for sub-temperate, sub humid agro-climatic condition using climatic and lysimeter data. The Food and Agriculture Organization (FAO) recommended crop coefficient values are modified for the local agro-climatic conditions. The field experiment was conducted in sub-temperate and sub-humid agro-climate of Solan, Himachal Pradesh, India. Actual crop evapotranspiration for different crop growth stages of wheat (Triticum-aestivum) has been obtained from water balance studies using lysimeter set-up. Field observed and computed individual-stage wise crop evapotranspiration values are compared, to identify the most suitable reference evapotranspiration model for computing crop evapotranspiration. Penman Monteith model shows close agreement with observed value with coefficient of determination, standard error estimate and average relative discrepancy values of 0.96, 13.69 and -5.8, respectively. Further, an effort has been made to compare the accuracy of various widely used methods under different climatic conditions.Keywords: crop coefficient, crop evapotranspiration, reference evapotranspiration, lysimeterDOI: 10.3965/j.ijabe.20130604.003Citation: Kumar R. Ecohydrologic modeling of crop evapotranspiration in wheat (Triticum-aestivum) at sub-temperate and sub-humid region of India. Int J Agric & Biol Eng, 2013; 6(4): 19－26.